The anti‐hepatic fibrosis effects of dihydrotanshinone I are mediated by disrupting the yes‐associated protein and transcriptional enhancer factor D2 complex and stimulating autophagy. (6th April 2017) - Ge, Maoxu; Liu, Hong; Zhang, Yixuan; Li, Naren; Zhao, Shuangshuang; Zhao, Wuli; Zhen, Yongzhan; Yu, Jianzhong; He, Hongwei; Shao, Rong‐guang
Abstract : Background and Purpose: Dihydrotanshinone I (DHI), a lipophilic component of traditional Chinese medicine Salvia miltiorrhiza Bunge, has various therapeutic effects. We investigated the anti‐fibrotic effect of DHI and its underlying mechanisms in vitro and in vivo . Experimental Approach: Rats subjected to bile duct ligation (BDL) were treated with DHI (25 mg·kg −1 ·day −1, i.p.) for 14 days. Serum biochemical and liver tissue morphological analyses were performed. The human hepatic stellate cell line LX‐2 served as a liver fibrosis model in vitro . Liver fibrogenic genes, yes‐associated protein (YAP) downstream genes and autophagy markers were examined using western blot and real‐time PCR analyses. Similar analyses were done in rat primary hepatic stellate cells (pHSCs). Autophagy flux was assessed by immunofluorescence. Key Results: In BDL rats, DHI administration attenuated liver necrosis, bile duct proliferation and collagen accumulation and reduced the expression of genes associated with fibrogenesis, including Tgfb1, Mmp‐2, Acta2 and Col1a1 . DHI (1, 5, 10 μmol·L −1 ) time‐ and dose‐dependently suppressed the protein level of COL1A1, TGFβ1 and α‐SMA in LX‐2 cells and rat pHSCs. Furthermore, DHI blocked the nuclear translocation of YAP, which inhibited the YAP/TEAD2 interaction and its downstream fibrogenic genes, connective tissue growth factor, SOX4 and survivin. This stimulated autophagic flux and accelerated the degradation of liver collagen. Conclusions and Implications: DHI exerts anti‐fibrotic effects in BDL rats, LX‐2 cells and rat pHSCs by inhibiting the YAP and TEAD2 complex and stimulating autophagy. These findings indicate that DHI may be a potential therapeutic for the treatment of liver fibrosis.